Water-absorbent resin and its manufacturing method

The water-absorbing resin with a fiber-modified layer via electrospinning addresses gel blocking issues, enhancing liquid penetration and permeability while maintaining absorption capacity, suitable for paper diapers.

JP7624481B2Active Publication Date: 2025-01-30TAIWAN SOKOU INDS KOFUN YUUGENKOUSHI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023112887
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-08-04
Filing Date
2023-07-10
Publication Date
2025-01-30
Estimated Expiration
2043-07-10

Smart Images

  • Figure 0007624481000002
    Figure 0007624481000002
  • Figure 0007624481000003
    Figure 0007624481000003
  • Figure 0007624481000004
    Figure 0007624481000004
Patent Text Reader

Abstract

To provide a superabsorbent polymer and a method for producing the same.SOLUTION: The superabsorbent polymer comprises a core structure, a shell layer covering the core structure and a fiber-modified layer covering an outer surface of the shell layer. With the fiber-modified layer, the superabsorbent polymer not only has good water absorption properties, but also has excellent liquid permeability and permeability.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a water-absorbent resin, and in particular to a water-absorbent resin having excellent water absorbency as well as liquid permeability and permeability, and a method for producing the same. [Background technology]

[0002] Water-absorbent resins are used in a wide range of applications, such as water retention agents in agriculture or horticulture, anti-dew coagulants in building materials, materials for removing water from petroleum, waterproof outer coating agents in cables, and personal hygiene products (e.g., paper diapers, feminine hygiene products, disposable towels, etc.), among which paper diapers are the main application.

[0003] In recent years, paper diapers have become thinner. Therefore, the development of the paper diapers is to increase the amount of absorbent resin (i.e., material with high bulk density and water absorption) while decreasing the amount of hydrophilic fiber (i.e., wood pulp or material with low bulk density). The paper diapers are made thinner by increasing the proportion of absorbent resin in the absorbent structure of the paper diaper. However, considering the actual usage of paper diapers, if the amount of absorbent resin increases and the amount of hydrophilic fiber decreases, the absorbent resin that absorbs a large amount of water will cause the strength of the colloidal gel after absorbing water to become soft, resulting in a defect of gel blocking, which significantly reduces the liquid diffusion of the paper diaper and affects the performance of the paper diaper.

[0004] Conventional methods for preventing gel blocking of water-absorbent resins include a method of performing a polymerization reaction using UV light to prevent gel blocking, followed by a secondary surface cross-linking reaction (US Patent US10,335,768), a method of effectively reducing the gel blocking phenomenon and improving the permeability of the water-absorbent resin that has absorbed a liquid by mixing a polyvalent metal salt (e.g., aluminum sulfate) with the water-absorbent resin and then performing a heating reaction (Japan Patent JP2001-523289A), a method of improving the gel blocking phenomenon by adding an aqueous solution of a polyvalent metal salt to the surface of a water-absorbent resin with a particle size of 5 μm to 500 μm and then heating the water-absorbent resin (Japan Patent JP2509087), and a method of improving the diffusibility and liquid permeability of the water-absorbent resin that has absorbed a liquid by mixing a water-soluble polyvalent metal powder, an adhesive, and a water-absorbent resin ( Chinese published patent CN1747751A, WIPO published patent WO2004 / 113452A, or US published patent US20170050170A), a method of imparting excellent permeability to a produced water absorbent resin by using an amino group-containing azo compound as a foaming agent in an acid group-containing monomer aqueous solution (US Patent US5985944), a method of reducing the solubility of dissolved gas in an aqueous monomer solution by adding a surfactant (e.g., polyoxyethylene sorbitan fatty acid ester) to an acid group-containing monomer aqueous solution (Japanese Patent JP6532894), or a method of improving the liquid permeability of a water absorbent resin by adding a nitrogen-containing polymer (e.g., N-vinylcarboxamide) or a solution thereof that can protonate nitrogen atoms to the water absorbent resin (US published patent US20050245684A).

[0005] Also, US Patent US7777093 describes that the liquid permeability of the water-absorbing resin can be improved by applying a thermoplastic polymer (e.g., a polymer such as polyurethane or polyester) to the surface of the water-absorbing resin. However, adding raw materials to the water-absorbing resin not only raises doubts about the safety of the raw materials, but also leads to an increase in overall costs and a decrease in other physical properties.

[0006] In addition, in order to improve the liquid permeability of the water-absorbent resin, a surface treatment step may be performed using a polyamine polymer in combination with polyvinylamine, polyallylamine, etc. (WIPO published patent WO2006082189A). However, the difficulty and cost of producing polyamine-coated particles, as well as their chemical and physical properties, are all related to the water absorption rate of the water-absorbent resin, so that an ideal water-absorbent resin is the result of a combination that is difficult to design.

[0007] In view of this, it is necessary to provide a water-absorbing resin and a method for producing the same in order to further improve the defect of gel blocking in the conventional water-absorbing resin and the method for producing the same. Summary of the Invention

[0008] Therefore, one aspect of the present invention provides a water-absorbent resin that can effectively eliminate the conventional defect of gel blocking by providing a fiber-modified layer on the surface of the shell layer of the water-absorbent resin.

[0009] Another aspect of the present invention provides a method for producing a water-absorbent resin, which improves the liquid flowability between resin particles by forming a fiber-modified layer of the water-absorbent resin in a spinning process, and improves the liquid permeability and permeability of the water-absorbent resin.

[0010] According to one aspect of the present invention, a water-absorbent resin is provided that includes a core structure, a shell layer that completely covers the core structure, and a fiber-modified layer that covers at least a portion of the outer surface of the shell layer, the fiber-modified layer including a plurality of fibers, the fibers being anisotropically laminated to the outer surface.

[0011] According to some embodiments of the present invention, the aforementioned fiber modification layer is continuously coated onto a portion of the outer surface of the shell layer.

[0012] According to some embodiments of the present invention, the fiber modification layer is discontinuously coated onto portions of the outer surface of the shell layer.

[0013] According to some embodiments of the present invention, the aforementioned fiber modification layer is completely coated on the outer surface of the shell layer.

[0014] According to one aspect of the present invention, there is provided a method for producing a water absorbent resin, the method including: first, a step of performing a free radical polymerization reaction on a water absorbent resin composition having an acid group-containing monomer aqueous solution, a crosslinking agent, and a polymerization initiator including a thermal decomposition initiator and / or a redox initiator, to form a crosslinked core structure; then, a step of performing a surface crosslinking reaction on the crosslinked core structure to form a shell layer on the crosslinked core structure so as to completely cover the crosslinked core structure; and, after the surface crosslinking reaction, a spinning process is performed to form a fiber modified layer on an outer surface of the shell layer, the fiber modified layer covering at least a part of the outer surface of the shell layer and including a plurality of fibers, thereby obtaining a water absorbent resin.

[0015] According to some embodiments of the present invention, the aforementioned spinning process includes first preparing a polymer solution containing a polymeric material and then subjecting the polymer solution to a spinning process to form these fibers.

[0016] According to some embodiments of the present invention, the molecular weight of the aforementioned polymeric material is between 10,000 g / mole and 500,000 g / mole.

[0017] According to some embodiments of the present invention, the aforementioned polymeric material has a hydrophilic-lipophilic balance (HLB) value of 11-19.

[0018] According to some embodiments of the present invention, the aforementioned spinning step is performed by electrospinning.

[0019] According to some embodiments of the present invention, the diameter of said fibers is less than 1000 nm.

[0020] By applying the water-absorbent resin and the manufacturing method thereof of the present invention, the shell layer of the core-shell structure of the water-absorbent resin and the fiber-modified layer provided on the surface of the shell layer are formed by the surface cross-linking reaction and the spinning process, so that the produced water-absorbent resin can have excellent water absorption, as well as excellent liquid permeability and permeability. Here, the spinning process may use electrospinning technology to form nanofibers so as to effectively increase the gaps between the resin particles, improve the fluidity of the liquid therein, and improve the liquid permeability and permeability. The nanofibers formed by electrospinning technology have a uniform diameter, so that the void structure of the fiber-modified layer can be effectively adjusted to eliminate the defects of conventional gel blocking and meet the application requirements of the water-absorbent resin. [Brief description of the drawings]

[0021] For a more complete understanding of embodiments of the present invention and its advantages, reference is now made to the following drawings, in which it is emphasized that the various features are for illustrative purposes only and are not drawn to scale. [Figure 1] 1 is a flowchart showing a method for producing a water-absorbent resin according to some embodiments of the present invention. [Figure 2A] 1 is a scanning electron microscope photograph of the water-absorbent resin of Example 1 of the present invention. [Figure 2B] 1 is a scanning electron microscope photograph of the water-absorbent resin of Example 3 of the present invention. [Figure 2C] 1 is a scanning electron microscope photograph of the water-absorbent resin of Example 5 of the present invention. [Figure 2D] 1 is a scanning electron microscope photograph of the water-absorbent resin of Example 8 of the present invention. [Figure 2E] 1 is a scanning electron microscope photograph of a water-absorbent resin of Comparative Example 1 of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] The making and using of the embodiments of the present invention are described in detail below. However, it will be appreciated that the many applicable inventive concepts provided in the embodiments may be embodied in a variety of specific contexts. The specific embodiments discussed are for illustrative purposes only and are not intended to limit the scope of the present invention.

[0023] The present invention provides a method for producing a water-absorbent resin, which improves the liquid permeability and permeability of the produced water-absorbent resin while maintaining water absorption, by producing nanofibers using electrospinning technology and coating the surface of the water-absorbent resin with the nanofibers. When the water-absorbent resin of the present invention is applied to absorbent products such as paper diapers, the defects of conventional gel blocking can be effectively avoided and the water-absorbency of the absorbent product can be maintained. Here, in the present invention, first, a water-absorbent resin composition is subjected to a free radical polymerization reaction to form a hydrocolloid gel, which is then sheared into small hydrocolloid gels, which are then dried with hot air at a temperature of 100°C to 250°C, crushed, and sieved to obtain a crosslinked core structure, and then the crosslinked core structure is subjected to a surface crosslinking reaction to coat the nanofibers to obtain the water-absorbent resin of the present invention.

[0024] The water-absorbent resin of the present invention can form nanofibers with a controllable void structure on the surface of the water-absorbent resin by electrospinning, so that there is a fiber-modified layer on the surface of the water-absorbent resin and the gaps between the resin particles are increased, thereby effectively improving the fluidity of the liquid, eliminating the defect of the conventional gel blocking, and allowing the water-absorbent resin to still have excellent water absorption.

[0025] Please refer to Figure 1, which shows a flow chart of a method for manufacturing a water-absorbing resin according to some embodiments of the present invention. In the method 100, a water-absorbing resin composition is subjected to a free radical polymerization reaction to form a crosslinked core structure, as shown in operation 110. Here, the water-absorbing resin composition includes an aqueous solution of an acid group-containing monomer, a crosslinking agent, and a polymerization initiator.

[0026] The acid group-containing monomer aqueous solution is obtained by dissolving an acid group-containing monomer compound in water. The acid group-containing monomer compound includes, but is not limited to, acrylic acid, methacrylic acid, and / or 2-acrylamido-2-methylpropanesulfonic acid. In some embodiments, the acid group-containing monomer compound may selectively include other water-soluble monomers having an acid group and an unsaturated double bond. For example, the other water-soluble monomers having an acid group and an unsaturated double bond may include maleic acid, fumaric acid, maleic anhydride, fumaric anhydride, and / or other suitable water-soluble monomers having an acid group and an unsaturated double bond. In other embodiments, the acid group-containing monomer compound may selectively include other hydrophilic monomers having an unsaturated double bond. For example, the other hydrophilic monomers having an unsaturated double bond may include acrylamide, methacrylamide, 2-carboxyethyl acrylate, 2-carboxyethyl methacrylate, methyl acrylate, ethyl acrylate, dimethylamine acrylamide, propylene acryloylaminotrimethylammonium chloride, and / or other suitable hydrophilic monomers having an unsaturated double bond. The amount of the hydrophilic monomer added is not particularly limited as long as it does not impair the physical properties of the water-absorbing resin. The selection of the above-mentioned monomer is not particularly limited to one type, and multiple types of monomers may be used in combination.

[0027] In some embodiments, the carboxylic acid group of the acid group-containing monomer compound can be partially neutralized to control the pH of the resulting water absorbent resin to be neutral or slightly acidic. The neutralizing agent used for neutralization may be a hydroxide or carbonate compound of an alkali metal element or an alkaline earth metal element. For example, the neutralizing agent includes, but is not limited to, sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, sodium bicarbonate, potassium bicarbonate, or an ammonia compound, and may be used alone or in combination of two or more. The carboxylic acid group of the acid group-containing monomer compound is partially neutralized to a sodium salt, a potassium salt, or an ammonium salt. In some embodiments, the neutralization concentration of the acid group-containing monomer aqueous solution may be 45 mol% to 85 mol%, preferably 50 mol% to 75 mol%. When the neutralization concentration of the acid group-containing monomer aqueous solution is in the above-mentioned range, the produced water absorbent resin is neutral or slightly acidic so as not to cause harm to the human body even if it comes into contact with the skin. In some embodiments, the pH of the acid group-containing monomer aqueous solution is 5.5 or more. When the pH of the acid group-containing monomer aqueous solution is 5.5 or more, the amount of residual monomer in the crosslinked core structure formed is small, which contributes to improving the physical properties of the water absorbent resin.

[0028] The concentration of the acid group-containing monomer aqueous solution when carrying out the free radical polymerization reaction is not particularly limited, but is preferably 20% by weight to 55% by weight, more preferably 30% by weight to 45% by weight. When the concentration of the acid group-containing monomer aqueous solution is within this range, the hydrocolloid gel formed by polymerization has an appropriate softness and viscosity, and therefore has excellent processability, and the amount of residual monomer in the hydrocolloid gel is small, so that the obtained water absorbent resin has excellent physical properties.

[0029] In some embodiments, the aqueous solution of the acid group-containing monomer may selectively contain a water-soluble polymer. In some embodiments, the water-soluble polymer may include, but is not limited to, partially or completely saponified polyvinyl alcohol, polyethylene glycol, polyacrylic acid, polyacrylamide, starch and / or starch derivatives (e.g., methyl cellulose, methyl cellulose acrylate and / or ethyl cellulose). Preferably, the water-soluble polymer may be starch and / or partially or completely saponified polyvinyl alcohol. When the amount of the aqueous solution of the acid group-containing monomer used is 100% by weight, the amount of the water-soluble polymer used may be 0% by weight to 20% by weight, preferably 0% by weight to 10% by weight, more preferably 0% by weight to 5% by weight. When the amount of the water-soluble polymer used is within this range, the production cost of the water-absorbing resin is reduced, but its water absorption is not affected, so that the application requirements can still be met.

[0030] The crosslinking agent may include a compound having at least two unsaturated double bond groups, a compound having at least two epoxy groups, other suitable crosslinking agents, or any combination of the above compounds. When performing a free radical reaction, the crosslinking agent can provide an appropriate degree of crosslinking to the crosslinked core structure formed, and can improve the processability of the resulting water absorbent resin. In some specific examples, the compound having at least two unsaturated double bond groups is N,N'-bis(2-propenyl)amine, N,N'-methylenebisacrylamide, N,N'-methylenebismethacrylamide, propylene acrylate, ethylene glycol diacrylate, polyethylene glycol diacrylate, ethylene glycol dimethacrylate, polyethylene glycol dimethacrylate, glycerol triacrylate, glycerol trimethacrylate, triacrylate obtained by adding ethylene oxide to glycerol, and ethylene oxide to glycerol. trimethacrylate, triacrylate with ethylene oxide added to trimethylolpropane, trimethacrylate with ethylene oxide added to trimethylolpropane, trimethacrylate with ethylene oxide added to trimethylolpropane, trimethacrylate with trimethylolpropane, trimethacrylate with trimethylolpropane, N,N,N-tris(2-propenyl)amine, ethylene glycol diacrylate, polyoxyethylene glycerin triacrylate, diethyl polyoxyethylene glycerin triacrylate, and / or dipropylene triglycol triacrylate. In some embodiments, the compound having at least two unsaturated epoxy groups may include, but is not limited to, sorbitol polyglycidyl ether, polyglycerol polyglycidyl ether, ethylene glycol diglycidyl ether, diethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, and / or diglycerol polyglycidyl ether. When the total content of the solids in the water-absorbing resin composition is taken as 100% by weight, the amount of the crosslinking agent used may be 0.001% by weight to 5% by weight, and preferably 0.01% by weight to 3% by weight.When the amount of the crosslinking agent used is within this range, the crosslinked core structure formed by the free radical polymerization reaction has excellent mechanical properties and is easy to machine, and the produced water-absorbent resin can still have excellent water absorption.

[0031] The polymerization initiator decomposes to generate free radicals, which induces the free radical polymerization reaction of the acid group-containing monomer compound and forms a hydrocolloid gel to obtain a crosslinked core structure. The polymerization initiator of the present invention may include, but is not limited to, a thermal decomposition initiator, a redox initiator, other suitable polymerization initiators, or any combination of the above materials. In some embodiments, the thermal decomposition initiator may include hydrogen peroxide, di-tert-butyl peroxide, acylamine peroxide, persulfate (e.g., ammonium salt or alkali metal salt, etc.), and / or azo compound (e.g., 2,2'-azobis(2-amidinopropane) dihydrochloride or 2,2'-azobis(N,N-dimethyleneisobutylamidine) dihydrochloride, etc.). In some embodiments, the redox initiator may include an acid sulfite, a thiosulfate, and / or an ascorbic acid or ferrous salt.

[0032] When the polymerization initiator includes both a thermal decomposition initiator and a redox initiator, the redox initiator decomposes first to generate free radicals, which can trigger the first stage of polymerization in the free radical polymerization reaction. At the same time, the reaction heat from the first stage of polymerization reaction can decompose the thermal decomposition initiator, which can trigger the second stage of polymerization reaction, and improve the reactivity of the free radical polymerization reaction.

[0033] The amount of the polymerization initiator is 0.001% by weight to 10% by weight, preferably 0.1% by weight to 5% by weight, based on the amount of the neutralized acrylate salt being 100% by weight. When the weight of the polymerization initiator is 0.001% by weight to 10% by weight, the free radical polymerization reaction has appropriate reactivity and is easy to control, and the degree of polymerization of the formed hydrocolloid gel is prevented from being too high, and the formation of agglomerated colloid blocks can be prevented.

[0034] The free radical polymerization reaction of the present invention can be carried out in a conventional batch reactor or a conveyor reactor. After carrying out the free radical polymerization reaction, the formed hydrocolloid gel is first sheared by a grinder into small hydrocolloid gels with a diameter of 2.0 mm or less, baked and dried, and then sieved. Preferably, the small hydrocolloid gels have a diameter of 1.0 mm or less.

[0035] When shearing, the particle size of the hydrocolloid gel is preferably 2.00 mm or less, more preferably 0.05 mm to 1.50 mm. Hydrocolloid gels with a particle size larger than 2.00 mm are returned to the reactor and crushed once more. When the hydrocolloid gels with a particle size larger than 2.00 mm are subsequently baked, the heat conduction effect is low, so that the finished product is likely to have a large amount of excess residual monomers and its physical properties are deteriorated. After the hydrocolloid gels with a particle size smaller than 0.05 mm are baked and crushed, the amount of fine powder in the finished product is likely to increase, and the quality of the finished product is deteriorated. According to the present invention, the narrower the particle size distribution of the acrylate colloid gel, the better the physical properties of the colloid gel after baking, and the easier it is to control the time and temperature of the subsequent baking.

[0036] The baking temperature may be 100°C to 180°C. If the baking temperature is less than 100°C, the baking time is too long, which is uneconomical. If the baking temperature is more than 180°C, the temperature is too high and the crosslinking agent is likely to crosslink early, so that the degree of crosslinking is too high in the subsequent drying process, making it difficult to effectively remove residual monomers.

[0037] After baking and drying, the product is sieved. The fixed particle size to be sieved is preferably 0.06 mm to 1.00 mm, more preferably 0.10 mm to 0.850 mm. Fine powders with a particle size smaller than 0.06 mm tend to increase the amount of dust in the finished product, while particles with a particle size larger than 1.00 mm tend to decrease the water absorption rate of the finished product. According to the present invention, the narrower the particle size distribution of the acrylate polymer, the more preferable.

[0038] After baking, drying, pulverizing and sieving to a fixed particle size, the crosslinked core structure of the present invention can be obtained.

[0039] Please continue to refer to Figure 1. After performing operation 110, the crosslinked core structure is subjected to a surface crosslinking reaction as shown in operation 120. The crosslinked core structure produced is an insoluble hydrophilic polymer having a uniform crosslinked structure therein. Generally, the surface of the crosslinked core structure is further crosslinked to improve the quality (e.g., absorption rate, colloidal strength, anti-caking property, and / or liquid permeability, etc.) of the resulting water absorbent resin. This surface crosslinking treatment utilizes a polyfunctional crosslinking agent capable of reacting with an acid group, and many patents have been provided so far, including, for example, a method of performing surface crosslinking treatment by dispersing a water-absorbent resin and a crosslinking agent in an organic solvent (JP1981-131608A, JP1982-44627A, JP1983-42602A, JP1983-117222A), a method of directly mixing a crosslinking agent and a crosslinking agent solution with a water-absorbent resin using inorganic powder for treatment (JP1985-163956A, JP1985-255814A), a method of adding a crosslinking agent and then performing steam treatment (JP1989-113406A), a method of performing surface treatment with an organic solvent, water, and a polyhydric alcohol (JP1989-292004A, U.S. Patent US6346569), and a method of using an organic solution, water, and an ether compound (JP1990-153903A). Although these surface treatment methods can improve the absorption speed and water absorption capacity under pressure, they also result in poor retention, which reduces their practical utility.

[0040] In the present invention, the surface cross-linking agent that can react simultaneously with the surface treatment includes, but is not limited to, polyols, polyamines, compounds having at least two epoxy groups, alkylene carbonates, and / or other suitable compounds. For example, the polyhydric alcohol may include glycerin, ethylene glycol, diethylene glycol, triethylene glycol, polyethylene glycol, and / or propylene glycol, the polyhydric amine may include ethylenediamine, diethylenediamine, and / or triethylenediamine, the compound having at least two epoxy groups may include sorbitol polyglycidyl ether, polyglycerol polyglycidyl ether, ethylene glycol diglycidyl ether, diethylene glycol diglycidyl ether, The alkylene carbonate may include polyethylene glycol diglycidyl ether and / or diglycerol polyglycidyl ether, and the alkylene carbonate may include ethylene carbonate, 4-methyl-1,3-dioxolane-2-one, 4,5-dimethyl-1,3-dioxolane-2-one, 4,4-dimethyl-1,3-dioxolane-2-one, 4-ethyl-1,3-dioxolane-2-one, 1,3-dioxan-2-one, 4,6-dimethyl-1,3-dioxan-2-one, and / or 1,3-dioxan-2-one. The above-mentioned surface crosslinking agents may be used alone or in combination of two or more. When the total content of the solid content in the water absorbent resin composition is 100% by weight, the amount of the surface crosslinking agent used is 0.001% by weight to 10% by weight, preferably 0.005% by weight to 5% by weight. When the amount of the surface cross-linking agent used is within this range, the above-mentioned effect of surface cross-linking is significantly improved, and the water-absorbent resin can still have good water absorbency and good physical properties.

[0041] When applying the surface cross-linking agent, depending on the type of the surface cross-linking agent, it may be added directly, or an aqueous solution of the surface cross-linking agent may be prepared and added, or an aqueous solution of the surface cross-linking agent in a hydrophilic organic solvent may be prepared and added. Here, the hydrophilic organic solvent is not particularly limited as long as it can form a solution. In some specific examples, the hydrophilic organic solvent may be, for example, methanol, ethanol, propanol, isobutanol, acetone, methyl ether, and / or diethyl ether. Preferably, the hydrophilic organic solvent may be methanol and / or ethanol (US Patent US6849665).

[0042] After carrying out the surface cross-linking reaction, the surface cross-linking agent can form a shell layer on the outer surface of the cross-linked core structure, and completely cover the cross-linked core structure. Then, as shown in operation 130 and operation 140 of Figure 1, a spinning process is carried out to form a fiber modification layer on the outer surface of the shell layer, to obtain the water absorbent resin of the present invention.

[0043] In the spinning process, the fiber-modified layer having nanofibers may be formed by techniques such as drawing, template synthesis, self-organization, and electrospinning. Among them, the electrospinning method has a wide range of usable raw materials and is easy to operate. The manufacturing method of electrospinning is to apply a high voltage electric field to the polymer solution, spray the polymer solution from the tip of a spinning needle, and after the solvent evaporates, the polymer in the solution precipitates and hardens to obtain a nano-dimensional fiber material.

[0044] Nanofibers can be efficiently produced by electrospinning. The principle is that non-Newtonian fluid can form a Taylor cone structure at the outlet of the spinning nozzle under the action of a high-voltage electric field, and the sprayed solution droplets can form micron-scale to nano-scale fibers, and the nanofibers, which have the appearance of irregularly shaped nonwoven fabrics, can be collected from the collection tray. Here, the spray flow rate is usually 0.001ml / min to 0.1ml / min.

[0045] Generally, electrospinning is carried out in an open environment, however, the nanofibers formed by electrospinning are subject to various environmental factors (e.g., environmental temperature, humidity, and / or wind speed, etc.), which may affect the appearance of the nanofibers, and the formed nanofibers may have defects such as non-uniform diameters (e.g., fibers containing a large amount of beading may be produced).

[0046] In order to effectively solve the influence of the open environment, the present invention performs electrospinning in a closed environment to effectively control the environmental factors. In the electrospinning device of the present invention, the spinning needle tip and the collection tray are installed in a closed box, so that nanofibers can be formed in a closed environment.

[0047] The spinning process of the present invention includes first preparing a polymer solution, and then performing a spinning process on the polymer solution to form a fiber-modified layer having nanofibers on the outer surface of the shell layer. Each of the nanofibers formed has a uniform diameter. In some embodiments, the diameter of the nanofibers formed is 1000 nm or less.

[0048] A polymer solution is a solution in which a polymer material is dissolved in a solvent. In order to effectively produce the nanofibers of the present invention, the weight average molecular weight (M w ) may be 10,000 g / mole to 500,000 g / mole, preferably 50,000 g / mole to 500,000 g / mole. When the weight average molecular weight of the polymer material is in this range, the prepared polymer solution has suitable viscosity and mechanical properties, which contributes to the continuous and stable formation of nanofibers, and the formed nanofibers are not easily broken, and the occurrence of beading defects can be avoided. In some embodiments, the hydrophilic-lipophilic balance value of the polymer material may be 11 to 19. When the hydrophilic-lipophilic balance value of the polymer material is in this range, the fiber-modified layer formed by the subsequent electrospinning can effectively improve the liquid permeability and permeability of the water-absorbent resin, and meet the application requirements. Preferably, the hydrophilic-lipophilic balance value of the polymer material is 13 to 18.

[0049] In some embodiments, the polymeric material includes, but is not limited to, polyvinylidene fluoride (FVPF), polyvinylidene fluoride-hexafluoropropylene copolymer, polyacrylonitrile, polystyrene, polyglycolic acid, polyvinylpyrrolidone, polyethylene oxide, polyoxyethylene, polyvinyl alcohol, polybutylene terephthalate, polyethylene terephthalate, polyvinyl acetate, polycaprolactone, polyethylene glycol, polycarbonate, polyvinyl chloride, cellulose acetate, nanocellulose, methylcellulose, polylactic acid, polypeptides, polyurethanes, polyoxyethylene, other suitable polymeric materials, or any combination of the above materials.

[0050] The solvent of the polymer solution is not particularly limited as long as it can dissolve the aforementioned polymeric material and can be efficiently evaporated during the spinning process. In some embodiments, the solvent of the polymer solution includes, but is not limited to, an alcohol-based solvent, an acetone-based solvent, an acid or ester-based solvent, other suitable solvents, or any combination of the above solvents. For example, examples of alcohol-based solvents include methanol, ethanol, 1-propanol, 2-propanol, hexafluoroisopropanol, triethylene glycol, tetraethylene glycol, and diphenylmethanol. Examples of acetone-based solvents include acetone, methyl ethyl ketone, methyl isobutyl ketone, methyl-n-propyl ketone, diisopropyl ketone, and diisobutyl ketone. Examples of acid or ester-based solvents include formic acid, methyl formate, ethyl formate, propyl formate, methyl benzoate, ethyl benzoate, methyl acetate, ethyl acetate, propyl acetate, dimethyl phthalate, diethyl phthalate, and dipropyl phthalate. Other suitable solvents include 1,1-dichloroethane, 1,2-dichloroethane, trichloroethane, dichloropropane, dibromoethane, bromomethane, bromoethane, acetonitrile, tetrahydrofuran, N,N-dimethylformamide, and water. The above-mentioned solvents may be used alone or in combination depending on the solubility of the polymeric material in the solvent.

[0051] Assuming that the total content of solids in the polymer solution is 100% by weight, the amount of the solvent used is 60% by weight to 95% by weight, preferably 5% by weight to 90% by weight. When the amount of the solvent used is within this range, the polymer material can be efficiently dissolved, and the polymer solution has an appropriate content of solids, which contributes to the formation of nanofibers.

[0052] In some embodiments, the polymer solution used is polyacrylonitrile (M w = 100,000 g / mole) in N,N-dimethylformamide, and the concentration of the polymer solution may be 10 wt %. Here, the preparation of the polymer solution is well known to those skilled in the art, so the description will be omitted here.

[0053] After preparing the polymer solution, a spinning process is carried out using a closed apparatus. The voltage required for electrospinning can be determined according to the type of the aforementioned polymer material. In some embodiments, when the polymer material includes polylactic acid, polyvinyl alcohol, polyurethane, polycaprolactone, polyoxyethylene, gelatin, etc., the voltage of the high-voltage electric field applied in the spinning process of the present invention may be 1000 volts to 30000 volts to effectively form nanofibers. When the voltage of the high-voltage electric field is in this range, the polymer material can be effectively spun into nanofibers, and the energy cost in the spinning process is low.

[0054] During the spinning process, the polymer solution is injected by a syringe and transported to the metal needle head for spinning in the closed box through a pipe line, and then the micro syringe pump is started under the above-mentioned high voltage electric field to spin the metal needle head to form nanofibers, which are collected from a collection tray located below the metal needle head.

[0055] Depending on the processability of the polymer material, the flow rate at the spinning nozzle in the spinning process (i.e., the injection rate of the polymer solution) can be adjusted. When the polymer material contains polylactic acid, polyvinyl alcohol, polyurethane, polycaprolactone, polyoxyethylene, gelatin, or the like, the flow rate at the spinning nozzle may be 0.001 ml / min to 1.0 ml / min, preferably 0.001 ml / min to 0.1 ml / min. When the flow rate at the spinning nozzle is in this range, the spinning process is economically beneficial, the solvent evaporates efficiently, nanofibers with a uniform diameter can be formed, and the occurrence of beading defects can be avoided.

[0056] The time of the spinning step is not particularly limited, and may be adjusted depending on the economical efficiency and the influence of the fiber modification layer on the water absorption of the water absorbent resin. In some specific examples, the time of the spinning step may be, for example, 10 min to 180 min, preferably 20 min to 120 min, and more preferably 30 min to 60 min. In these specific examples, the obtained water absorbent resin has effectively improved liquid permeability and permeability, and has good water absorption.

[0057] The nanofibers formed in the spinning process of the present invention have a uniform diameter. In some embodiments, the diameter of the formed nanofibers may be 10 nm to 1000 nm, preferably 50 nm to 1000 nm. When the diameter of the nanofibers is in this range, the polymer solution is less likely to cause gel blocking defects at the metal needle head, and the permeability of the formed water absorbent resin can be effectively improved.

[0058] When carrying out the above-mentioned spinning process, the water-absorbing particles having a shell layer formed by the surface cross-linking reaction are laid on a collection tray in a closed box, so that the nanofibers formed by the spinning process cover the surface of the water-absorbing particles (i.e., the outer surface of the shell layer) and form a fiber-modified layer on the surface of the water-absorbing particles, thereby forming the water-absorbing resin of the present invention. Here, the formed nanofibers are anisotropically deposited on the surface of the water-absorbing particles.

[0059] In the produced water absorbent resin, the nanofibers do not need to completely cover the outer surface of the shell layer, and can effectively improve the liquid permeability and permeability of the water absorbent resin, and the water absorbent resin also has good water absorption. Thus, the fiber modification layer formed by the nanofibers may cover only a part of the outer surface of the shell layer, and the fiber modification layer formed by the nanofibers may be a continuous membrane layer or a discontinuous membrane layer. In other words, within a specific range on the surface of the shell layer, the fiber modification layer attached to this specific range may be a continuous membrane layer or a discontinuous membrane layer (i.e., the fiber modification layer covers only a part of the area of ​​this specific range, and these areas are not connected to each other).

[0060] In other embodiments, the fiber modification layer formed by the nanofibers completely covers the shell layer. In these embodiments, since the outer surface of the shell layer is completely covered by the fiber modification layer, the water absorbent resin formed has better liquid penetration and permeability, as well as good water absorption.

[0061] In the spinning process of the present invention, the nanofibers formed can be bonded to the surface of water-absorbing particles with high water absorption after surface cross-linking treatment, and the water-absorbing resin produced thereby has excellent liquid permeability, permeability, and water absorption at the same time. As a result, the water-absorbing resin formed does not suffer from gel blocking after absorbing a large amount of water, and has good water absorption. By utilizing the characteristics of the nanofibers that meet the conditions of the present invention, the water-absorbing resin with high liquid permeability and permeability can be produced, and is applied to various sanitary products, agricultural and food freshness-preserving water absorbents.

[0062] The water-absorbing resin produced in the present invention and sanitary products produced with this water-absorbing resin can be preferentially applied to paper diapers, particularly low-concentration pulp paper diapers (fluffless; using a large amount of water-absorbing resin at the same time) and adult paper diapers. Conventional water-absorbing resins, when applied to paper diapers, do not have the advantage of improving liquid permeability and permeability without reducing the water absorption of the water-absorbing resin, but the water-absorbing resin produced in the present invention can effectively solve this problem.

[0063] The object of the present invention is to provide a simple method for producing a water-absorbent resin, and the water-absorbent resin produced by such a method can improve the liquid permeability and permeability without decreasing the water absorption of the water-absorbent resin. The production method of the present invention includes at least the steps of (a) forming an internal crosslinked structure of the water-absorbent resin by a free radical polymerization reaction of an aqueous solution of an acid group monomer, (b) adding a surface crosslinking agent to perform a surface crosslinking treatment to form a shell layer structure of the water-absorbent resin, (c) preparing a polymer solution for forming nanofibers, and (d) attaching the nanofibers to the shell layer surface of the water-absorbent resin by an electrospinning process.

[0064] The following examples are provided to illustrate the application of the present invention, but are not intended to limit the present invention. Those skilled in the art may make various changes and modifications without departing from the spirit and scope of the present invention.

[0065] (Preparation of Water-Absorbing Particles)

[0066] Preparation Example 1

[0067] First, in a 2000cc Erlenmeyer flask, 437.5g of 48% sodium hydroxide solution is gradually added to 540g of acrylic acid and 583.2g of water. The drop ratio of sodium hydroxide to acrylic acid is set to within the range of 0.85-0.95, the drop time is set to 2 hours, and the temperature of the neutralization reaction system in the flask is maintained at 15°C to 40°C, so that the monomer concentration in the aqueous solution is 42% by weight. sexlessA saturated monomer solution is obtained in which 70 mol % of acrylic acid is neutralized with sodium acrylate.

[0068] Then, 0.9 g of N,N'-methylenebisacrylamide is added to the aqueous unsaturated monomer solution, and the temperature is maintained at 20° C. Then, 0.3 g of hydrogen peroxide, 3.6 g of sodium bisulfite, and 3.6 g of ammonium persulfate initiator are added to carry out the reaction.

[0069] After the reaction is completed, the produced hydrocolloid gel is pulverized with a cutter mill, and small colloid gels with a particle size of 2 mm or less are sieved. Then, the hydrocolloid gel is dried at 130°C. After drying for 2 hours, the hydrocolloid gel is sieved with a sieve with a fixed particle size of 0.1 mm to 0.85 mm to obtain a powdered water absorbent resin. As a result of measuring the retention force by the following evaluation method, the retention force of the powdered water absorbent resin of Preparation Example 1 is 41.2 g / g.

[0070] Weigh out powdered water-absorbent resin (200 g), add a mixed aqueous solution (5 g) of ethylene glycol, 1,4-butanediol (manufactured by Taiwan Plastics Co., Ltd.) and methanol in a ratio of 1 / 1 / 0.5, and heat-treat at 150° C. for 1 hour. After cooling, obtain water-absorbent particles of Preparation Example 1, whose retention power is 32.7 g / g.

[0071] In addition, the water absorbency of the water absorbent particles of Preparation Example 1 was evaluated by the following evaluation method, and the water absorption capacity under pressure of the water absorbent particles of Preparation Example 1 was 22.5 g / g, the residual monomer was 378 ppm, the T20 was 380 seconds, the U20 was 26.6 g / g, and the GBP was 7.0 Darcy.

[0072] Preparation Example 2

[0073] First, in a 2000cc Erlenmeyer flask, 437.5g of 48% sodium hydroxide solution is gradually added to 540g of acrylic acid and 583.2g of water. The drop ratio of sodium hydroxide to acrylic acid is set to within the range of 0.85-0.95, the drop time is set to 2 hours, and the temperature of the neutralization reaction system in the flask is maintained at 15°C to 40°C, so that the monomer concentration in the aqueous solution is 42% by weight. sexless A saturated monomer solution is obtained in which 70 mol % of acrylic acid is neutralized with sodium acrylate.

[0074] Then, 1.3 g of polyethylene glycol diacrylate (molecular weight 538) is added to the aqueous unsaturated monomer solution, and the temperature is maintained at 20° C. Then, 0.3 g of hydrogen peroxide, 3.6 g of sodium bisulfite, and 3.6 g of ammonium persulfate initiator are added to carry out the reaction.

[0075] After the reaction is completed, the produced hydrocolloid gel is pulverized with a cutter mill, and small colloid gels with a particle size of 2 mm or less are sieved. Then, the hydrocolloid gel is dried at 130°C. After drying for 2 hours, the hydrocolloid gel is sieved with a sieve with a fixed particle size of 0.1 mm to 0.85 mm to obtain a powdered water absorbent resin. As a result of measuring the retention force by the following evaluation method, the retention force of the powdered water absorbent resin of Preparation Example 2 is 41.6 g / g.

[0076] A powdered water-absorbing resin (200 g) is weighed out, and a mixed aqueous solution (5 g) of ethylene glycol, 1,4-butanediol, and methanol in a ratio of 1 / 1 / 0.5 is added, and the mixture is heated at 150° C. for 1 hour. After cooling, the water-absorbing particles of Preparation Example 2 are obtained, and the retention power is 33.7 g / g.

[0077] In addition, the water absorbency of the water absorbent particles of Preparation Example 2 was evaluated using the following evaluation method, and the water absorption capacity under pressure of the water absorbent particles of Preparation Example 2 was 24.9 g / g, the residual monomer was 433 ppm, the T20 was 300 seconds, the U20 was 27.8 g / g, and the GBP was 6.9 Darcy.

[0078] Preparation of water-absorbent resin

[0079] Example 1

[0080] First, the polymer solution of Example 1 was prepared. This polymer solution contained polyvinyl alcohol (M w94,000g / mole, Merck, model number 341584) was dissolved in water and the concentration was adjusted to 10% by weight. Then, the water-absorbing particles (100g) of Preparation Example 1 were placed on an electrospinning collection tray, and the prepared polymer solution was injected into a syringe. Next, the high voltage electric field was controlled to 10,000 volts, and the flow rate of the micro syringe pump was adjusted to 0.1ml / min to perform the electrospinning process. After 15 minutes of spinning time, the water-absorbing resin of Example 1 could be obtained from the collection tray, and the water-absorbing ability of the water-absorbing resin of Example 1 was evaluated by the following evaluation method, and the evaluation results are shown in Table 1, and the explanation is omitted here.

[0081] Examples 2 to 10

[0082] In Examples 2 to 10, the same manufacturing method as that of the water-absorbent resin in Example 1 is used, but the difference is that the electrospinning parameters are changed in Examples 2 to 5, and the composition of the polymer solution and the electrospinning parameters are changed in Examples 6 to 10. Here, the polymer solution used in Examples 6 to 10 is polyvinyl alcohol (M w 94,000 g / mole; Merck, model number 341584) was dissolved in water and the concentration was adjusted to 10% by weight. The conditions and evaluation results of Examples 2 to 10 are shown in Table 1, and a description thereof will be omitted here.

[0083] Comparative Example 1

[0084] First, in a 2000cc Erlenmeyer flask, 437.5g of 48% sodium hydroxide solution is gradually added to 540g of acrylic acid and 583.2g of water. The drop ratio of sodium hydroxide to acrylic acid is set to within the range of 0.85-0.95, the drop time is set to 2 hours, and the temperature of the neutralization reaction system in the flask is maintained at 15°C to 40°C, so that the monomer concentration in the aqueous solution is 42% by weight. sexless A saturated monomer solution is obtained in which 70 mol % of acrylic acid is neutralized with sodium acrylate.

[0085] Then, 0.9 g of N,N'-methylenebisacrylamide is added to the water-soluble unsaturated monomer solution, and the temperature is maintained at 20° C. Next, phenol (100 ppm) is added to the water-soluble unsaturated monomer solution, and 0.3 g of hydrogen peroxide, 3.6 g of sodium bisulfite, and 3.6 g of ammonium persulfate initiator are added to carry out the reaction.

[0086] After the reaction is completed, the produced hydrocolloid gel is pulverized with a cutter mill, and small colloid gels with a particle size of 2 mm or less are sieved. Then, the gel is dried at 130°C. After drying for 2 hours, the gel is sieved with a sieve with a fixed particle size of 0.1 mm to 0.85 mm to obtain a powdered water absorbent resin, and the retention force was measured to be 41.2 g / g.

[0087] A powdered water absorbent resin (200 g) is weighed out, and a mixed aqueous solution (5 g) of ethylene glycol, 1,4-butanediol, and methanol in a ratio of 1 / 1 / 0.5 is added thereto, and the mixture is heated at 150° C. for 1 hour. After cooling, the water absorbent resin of Comparative Example 1 is obtained. The evaluation results are shown in Table 1, and the explanation is omitted here.

[0088] Comparative Example 2

[0089] Comparative Example 2 uses the same manufacturing method as the water absorbent resin of Comparative Example 1, but the difference is that in Comparative Example 2, 0.2 g of silica (manufactured by Evonik, product number A200) is further used to perform surface treatment on the water absorbent resin obtained. The evaluation results are shown in Table 1, and the explanation is omitted here.

[0090] Evaluation method

[0091] In the following evaluation methods, unless otherwise specified, the evaluation is performed in an environment of room temperature (for example, 21° C. to 25° C.) and relative humidity of 35% to 55%, and the water-absorbing resin needs to be mixed thoroughly before evaluation.

[0092] 1. Fiber diameter

[0093] Fiber diameter is measured using a transmission electron microscope in a manner well known to those skilled in the art.

[0094] 2.Holding power

[0095] Centrifuge Retention Capacity (CRC) is tested in accordance with the measurement method ERT 441.3(10) specified by the European Disposables and Nonwovens Association (EDANA).

[0096] 3. Water absorption rate under pressure

[0097] Absorption against pressure (AAP) is tested according to the measurement method of ERT 442.3(10) specified by EDANA. When the absorption against pressure is measured for 60 minutes under a pressure of 4.9 kPa against a sodium chloride aqueous solution with a concentration of 0.9% by weight, it is preferable to preferentially select one having an absorption of 15 g / g or more, more preferably 20 g / g to 30 g / g.

[0098] 4. Residual monomers

[0099] Residual Monomers (RAA) shall be tested in accordance with the measurement method prescribed by EDANA, ERT 410.3(10).

[0100] 5. T20 and U20

[0101] T20 and U20 are measured using the dynamic effective permeability and uptake kinetics test method (K(t) test method).

[0102] The measurement method involves measuring the time-dependent effective permeability (K(t)), the uptake kinetics under pressure of a hydrocolloid layer of absorbent polymer particles or a structure containing such absorbent particles. The purpose of this method is to evaluate the ability of hydrocolloids of absorbent polymer particles or structures such as absorbent products containing them to distribute liquids throughout the structure when the polymer is present in the absorbent product at high concentration and under mechanical pressure. Darcy's law and steady flow method are used here to calculate the expression of effective permeability, the details of which are well known to those skilled in the art. For example, this measurement method may be referred to PK Chatterjee, Elsevier, Absorbency (1982), pages 42-43, and Chemical Engineering, Vol. II, 3rd Edition, JM Coulson and JF Richardson, Pergamon Press (1978), pages 122-127.

[0103] The equipment used in the above method is called a Time Dependent Permeability Tester and may be a product manufactured by BRAUN GmbH, model number 03-080578.

[0104] T20 is measured and calculated using the formula used in the K(t) test method mentioned above. The test time is the time (in seconds) from 0 seconds until the sample reaches an intake of 20g / g, and the test method is according to the contents of the Chinese published patent CN103619291A.

[0105] U20 is calculated using the formula used in the K(t) test method described above. The intake amount (unit: g / g) of the sample after 20 minutes is analyzed, and the test method is performed according to the contents of the Chinese published patent CN103619291A.

[0106] 6. Free Swelling Gel Bed Permeability (FSGBP)

[0107] Free swelling gel bed permeability (FSGBP) is the amount of liquid permeated (unit: Darcy) obtained by a gel bed permeability tester under the condition that the water absorbent resin particles are freely swelling. "Free swelling" means that the water absorbent resin is allowed to swell without being subjected to a swelling restraint load, and is also called gel bed permeability (GBP) under swelling pressure of 0 psi, and the test method is tested according to the contents described in US Patent US8822582.

[0108] [Table 1]

[0109] As can be seen from Table 1, compared with Preparation Example 1 and Preparation Example 2, the water absorbent resins of Examples 1 to 10 manufactured by the electrospinning process have excellent liquid permeability and permeability because the evaluation results of T20, U20, and GBP are all improved. In Comparative Example 1, the liquid permeability of the water absorbent resin could be improved by adding phenol in the surface cross-linking reaction, but the water absorption was reduced and it was not possible to provide excellent permeability. In Comparative Example 2, the liquid permeability of the water absorbent resin could be improved by performing surface treatment on the water absorbent resin using silica powder, but the absorption capacity under pressure was significantly reduced and it did not have good liquid permeability. Apparently, the water absorbent resin manufactured by forming a fiber modification layer by electrospinning and performing surface treatment on the water absorbent resin has good liquid permeability and permeability as well as good water absorption.

[0110] Please refer to Figures 2A to 2E. They respectively show scanning electron microscope photographs of the water-absorbent resins of Example 1, Example 3, Example 5, Example 8, and Comparative Example 1 of the present invention. In them, the magnification of Figures 2A to 2D is 1000 times, and the scale gauge represents 50.0 μm, and the magnification of Figure 2E is 120 times, and the scale gauge represents 300 μm. Compared with Figure 2E (water-absorbent resin of Comparative Example 1), the water-absorbent resin of Figures 2A to 2D has a fiber-modified layer in which nanofibers are laminated on the surface, and a part of the shell layer of the water-absorbent resin is not covered with the fiber-modified layer. Furthermore, as can be seen from the evaluation results in Table 1, both the liquid permeability and permeability of the water-absorbent resin were improved, so that the water-absorbent resin obtained by simply covering a part of the surface shell layer with the fiber-modified layer of the present invention can have good liquid permeability and permeability, and also good water absorption.

[0111] As can be seen from the above examples, the advantage of the superabsorbent resin having excellent liquid permeability and permeability and the manufacturing method thereof of the present invention is that by using electrospinning technology to perform a surface treatment process on the superabsorbent resin, and based on the characteristics of high porosity and high specific surface area of ​​the nanofibers, the superabsorbent resin can be endowed with liquid permeability and permeability at the same time, and can be applied to various personal hygiene products such as ultra-thin baby diapers or adult diapers.

[0112] The present invention has been disclosed above based on the embodiments, but it is not limited to the present invention, and a person skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention, and therefore the protection scope of the present invention is based on that defined in the appended claims. [Explanation of symbols]

[0113] 100 ways 110, 120, 130, 140 operations

Claims

1. A core structure; a shell layer completely covering the core structure; A fiber modification layer covering at least a portion of the outer surface of the shell layer; Equipped with the fiber modification layer comprises a plurality of fibers of a polymeric material; the fibers are anisotropically laminated on the outer surface; The molecular weight of the polymeric material is between 10,000 g / mole and 500,000 g / mole; The polymeric material has a hydrophilic-lipophilic balance (HLB) value of 11 to 19; The diameter of the fiber is 689 nm or more and 820 nm or less, the fibers are electrospun nanofibers; Gel bed permeability (GBP) is 11.4 Darcy or more and 19.8 Darcy or less; Water-absorbing resin.

2. The water-absorbent resin according to claim 1 , wherein the fiber modification layer is continuously coated on a portion of the outer surface of the shell layer.

3. The water-absorbent resin according to claim 1 , wherein the fiber modification layer is discontinuously coated on a plurality of portions of the outer surface of the shell layer.

4. The water-absorbent resin according to claim 1 , wherein the fiber modification layer is completely coated on the outer surface of the shell layer.

5. A step of carrying out a free radical polymerization reaction on a water absorbent resin composition including an acid group-containing monomer aqueous solution, a crosslinking agent, and a polymerization initiator including a thermal decomposition initiator and / or a redox initiator to form a crosslinked core structure; performing a surface cross-linking reaction on the cross-linked core structure to form a shell layer on the cross-linked core structure, the shell layer completely covering the cross-linked core structure; After the surface crosslinking reaction, a spinning process is performed to form a fiber modified layer on the outer surface of the shell layer, the fiber modified layer covering at least a part of the outer surface and including a plurality of fibers, to obtain a water absorbent resin; Including, The gel bed permeability (GBP) of the water-absorbent resin is 11.4 Darcy or more and 19.8 Darcy or less, The spinning process comprises: preparing a polymer solution comprising a polymeric material, the polymeric material having a molecular weight of 10,000 g / mole to 500,000 g / mole and a hydrophilic lipophilic balance (HLB) of 11 to 19; performing a spinning process on the polymer solution to form the fibers, the fibers being electrospun nanofibers, the fibers having a diameter of 689 nm to 820 nm; Including, A method for producing a water-absorbent resin.

6. The method for producing a water-absorbent resin according to claim 5, wherein the polymeric material comprises polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer, polyacrylonitrile, polystyrene, polyglycolic acid, polyvinylpyrrolidone, polyethylene oxide, polyoxyethylene, polyvinyl alcohol, polybutylene terephthalate, polyethylene terephthalate, polyvinyl acetate, polycaprolactone, polyethylene glycol, polycarbonate, polyvinyl chloride, cellulose acetate, nanocellulose, methylcellulose, polylactic acid, polypeptide, and / or polyurethane.

7. The method for producing an absorbent resin described in claim 5, wherein the spinning process is carried out in a sealed environment.

8. The method for producing an absorbent resin described in claim 5, wherein the spinning process includes a process of applying a high-voltage electric field to the polymer solution.

Citation Information

Patent Citations

  • Textile composite materials containing nanofiber nonwoven fabrics

    JP2013540460A

  • Sanitary article

    WO2020003935A1